Toxicity and source identification of pollutants in an urban river in Bangladesh - Islam, M. Shahidul; Nakagawa, Kei; Abdullah-Al-Mamun, M.; Siddique, Md. Abu Bakar; Berndtsson, Ronny (Environmental Earth Sciences, 2023)
Urban rivers in Asian developing countries are becoming increasingly polluted due to industrialization and lacking treatment of wastewater. We investigated toxicity and likely sources of pollutants for the urban Shitalakshaya River, Bangladesh. Physiochemical variables and heavy metals were examined in water and sediment of an urban river section in Narayanganj City. The spatial distribution of quality indices and cluster groups indicates that the river’s downstream urban-affected areas are the most contaminated. Water and sediment quality guidelines indicate that COD, TSS, Fe, Pb, Zn in water, and Pb, Co, Ni, Cu, Zn, and particularly Pb and Cu in sediment, pose a serious threat to the aquatic ecosystem and human health in the area. Correlation, principal component (PCA), and cluster analysis (CA) indicate that the sources of Mn and Cd are geogenic, COD, TSS, Pb, Zn, Cu anthropogenic, and Fe, Ni, Co both geogenic and anthropogenic. The main anthropogenic pollution sources of the study area are municipal and industrial wastewater, boat and car traffic, runoff from agricultural areas, and stormwater runoff.